Prevalence of Partial Edentulism and Awareness to Restore the Same among the Patients Visiting a Tertiary Dental Care Centre in Ambala, Haryana, India: A Cross-sectional Study - Satvika Prasad; Sandeep Garg (Journal of Clinical and Diagnostic Research)
Introduction: Dental health is essential for overall well-being, affecting many aspects of an individual’s life, including physical health, social interactions and self-esteem. One significant issue in dental health is partial edentulism, which is the condition characterised by the loss of one or more natural teeth. A comprehensive understanding of partial edentulism necessitates a thorough exploration of its epidemiology. These studies not only shed light on the extent of the issue but also provide valuable insights into demographic patterns, contributing factors and disparities that may exist across different populations. Aim: To assess the prevalence of partial edentulism and the awareness of options for restoration among patients visiting a tertiary dental care centre in Haryana, India. Additionally, to evaluate the association of partial edentulism with socio-demographic factors, including age, gender, education level and total family income. Materials and Methods: This cross-sectional study was carried out at MM College of Dental Sciences and Research, Mullana, Ambala, Haryana, India. The duration of the study was six months (June 2022 to November 2022). A total of 507 patients were assessed. Questions regarding general information, economic status, reasons for the loss of teeth and the types of treatment taken for missing teeth were asked. Patients were also examined clinically for missing teeth and the type of prosthesis used. The collected data was then tabulated, analysed and subjected to a Chi-square test to evaluate the relationship of partial edentulism with socio-demographic factors. Results: The prevalence of partial edentulism among the study population was 72.90%. The major reason for tooth loss was caries, followed by caries coupled with periodontal problems. Most of the partially edentulous patients were not using any prosthesis and the major reasons for this were a lack of awareness, the cost of treatment, or the patients not feeling any requirement for a prosthesis. The association of partial edentulism with age, education level and total family income per month was found to be statistically significant (p<0.05), except for the gender of the patients. Conclusion: It can be concluded that the prevalence of partial edentulism was 72.9% and a significant association was found between partial edentulism and socio-demographic factors. However, no association was observed in relation to gender.